Density Functional Study on Benzene, Toluene, Ethylbenzene and Xylene Adsorptions on ZnO(100) Surface - Nugraha Nugraha; Adhitya Gandaryus Saputro; Mohammad Kemal Agusta; Fiki Taufik Akbar; Aditya Dimas Pramudya (Molekul, 2019)
We study the interaction between benzene, toluene, ethylbenzene and xylene (BTEX) molecules with ZnO(100) surface by means of density functional theory-based calculations. We find that these interactions result in the physical adsorptions of BTEX gases with adsorption distances larger than 2 Å. These adsorptions are governed by the van der Waals interaction instead of the covalent interaction. We also find that the trend of the strength of BTX adsorptions on ZnO(100) surface  is in line with the experimental trend of sensitivity of ZnO material towards BTX gases (benzene < tolune < xylene). We explain this relation by using one of the sensing mechanism within the ionosorption model. By using this relation, we also predict that the response of ZnO towards ethylbenzene will be similar to the response towards toluene since these two molecules have similar adsorption energies on ZnO(100) surface.